Singular Frequencies in Rectangular Fluctuations in the IEC Flickermeter - Ruiz, J.; Gutierrez, J.J.; Irusta, U. (IEEE transactions on power delivery, 2007)
A detailed observation of the IEC flickermeter subject to rectangular voltage fluctuations indicates the presence of small discontinuities for a set of fluctuation frequencies. These discontinuities are not observed in the real lamp-eye-brain model. This work provides the theoretical framework for the analysis of this phenomenon, a consequence of the nonlinear variance estimator model used in block 4 of the flickermeter. This effect has a limited impact on the field performance of the flickermeter but should be avoided from a conceptual point of view